Pelaksanaan Pembelajaran Pendidikan Jasmani Adaptif bagi Anak dengan Hambatan Fisik dan Motorik - Johandri Taufan; Ardisal Ardisal; Damri Damri; Arise Arise (Jurnal Pendidikan Kebutuhan Khusus, 2018)
This research to describe the implementation of adaptive sports education for physical and motoric X disability students in SDN X. This Research use descriptive qualitative method. Data collecting technique used in form of observation, interview and documentation study. Research subject are physical and motoric X disability students and teacher sports education initially called Z. Result of research indicated that school there is no special treatment in making learning program design, but in its implementation there are some different activities which will be given to physical and motoric X disability students without diminishing the meaning and purpose of its learning.